Zwei Sonaten in Form von Fantasien für das Pianoforte componirt von L. van Beethoven. Op. 27 ... No. 2 (Cis moll. Ut # min). Neue von Julius Knorr besorgte Ausgabe - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::::::::::::; Knorr, Julius, 1807-1861:::Contributor:::::::::::: (Joh. André; Offenbach am Main; Germany, 2022)
Revised edition of the Piano Sonata no. 14 in C# minor, op. 27, no. 2, published in the mid-nineteenth century by Johann André, edited by Julius Knorr.